Influence of Heavy Metal Salts on the Morphology of the Spleen (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The spleen exhibits a high level of reactivity with cytological restructuring of its immunocompetent structures under the influence of various endo- and exogenous factors, including heavy metals. Currently, it is known that the adaptive immune function, which determines the cellular and humoral homeostasis of the organism, is carried out by the organs of the immune system. Its morphological basis is lymphoid tissue, organized into functional formations, the largest of which is the spleen. This article presents a review of the literature on the influence of heavy metal salts on the morphology of the spleen.